DO PATIENTS WITH VARYING DEMOGRAPHIC AND REGIONAL CHARACTERISTICS EQUALLY MISS APPOINTMENTS ACROSS DENTAL SPECIALTIES? - Albaloushi, Hind M.; Da’ar, Omar (European Scientific Journal, ESJ, 2015)
Objectives: Since dental practice is unique and procedure-based, understanding the problem of missed dental appointment among patients in Health care facilities is crucial. The main purpose of this study was to understand whether patients with varying demographic, regional, and appointment characteristics equally missed dental appointments across dental specialties at King Faisal Specialist Hospital & Research Center (KFSH&RC), Riyadh. Method: After institutional approval, we retrospectively analyzed patientsâ€™ missed dental appointments. We selected a sample of 3185 patients with â€œNo showâ€ or missed dental appointments for 2012. We employed chi-square goodness of fit test to establish whether there were statistically significant relationships between the type of dental specialty a patient missed and various patient characteristics. Additionally, we employed Cramerâ€™s V to measure the strength of the relationship. Both techniques were useful in making statistical inferences from the data about the larger population based on the sample. Results: The findings showed that there are statistically significant relationships between the type of dental specialty a patient missed and various patient characteristics. Demographic, regional, registration characteristics of patients, appointment seasons and sessions, and chance of missed appointment in the various dental specialties are associated. However, with exception of age, all the other factors appear to have small effect on chance of missed appointments across dental specialties. Conclusion: With current problem of â€˜no showâ€™, the findings of this study is expected to inform KFSH&RC and other institutions to establish policies and guidelines to improve both the rate of "honored" appointments and minimize the many unused visit hours.